Topographic staging of tau positron emission tomography images - Schwarz, Adam J.; Shcherbinin, Sergey; Slieker, Lawrence J.; Risacher, Shannon L.; Charil, Arnaud; Irizarry, Michael C.; Fleisher, Adam S.; Southekal, Sudeepti; Joshi, Abhinay D.; Devous, Michael D.; Miller, Bradley B.; Saykin, Andrew J. (Alzheimer's & dementia : diagnosis, assessment & disease monitoring, 2018)
It has been proposed that the signal distribution on tau positron emission tomography (PET) images could be used to define pathologic stages similar to those seen in neuropathology. Three topographic staging schemes for tau PET, two sampling the temporal and occipital subregions only and one sampling cortical gray matter across the major brain lobes, were evaluated on flortaucipir F 18 PET images in a test-retest scenario and from Alzheimer's Disease Neuroimaging Initiative 2. All three schemes estimated stages that were significantly associated with amyloid status and when dichotomized to tau positive or negative were 90% to 94% concordant in the populations identified. However, the schemes with fewer regions and simpler decision rules yielded more robust performance in terms of fewer unclassified scans and increased test-retest reproducibility of assigned stage. Tau PET staging schemes could be useful tools to concisely index the regional involvement of tau pathology in living subjects. Simpler schemes may be more robust.